The Ijtihad Pada Era Kontemporer: Ijtihad Para Era Kontemporer - Muhammad Imron; Tri Wahyu Hidayat (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
This article examines the definition of ijtihad, the law of ijtihad, the division of ijtihad, the method of ijtihad, the requirements of mujtahid, the characteristics of contemporary ijtihad, and examples of the application of ijtihad in the contemporary era. As for the discussion of examples of the application of ijtihad methods in contemporary cases, the author takes the example of "abstention in elections". Abstention in elections on the grounds that there are no good or worthy candidates to become leaders while there is no other way to appoint leaders is wrong because it sacrifices daruriyat for the sake of hajiyat and tahsiniyat interests. So the best attitude in the election is to choose the best candidate with an objective assessment, not with the aim of achieving personal and group interests. If none of the candidates is good or all of them are bad according to the judgement of the voter concerned, then the voter must choose the candidate with the least badness. If the process and steps of ijtihad have been gone through, then it can be concluded and determined that abstaining from voting in elections on the grounds that there are no good or worthy candidates to become leaders while there is no other way to appoint leaders except through elections is haram.